DAMPAK KETERBATASAN AKSES TERHADAP REHABILITASI NARAPIDANA DISABILITAS DI LEMBAGA PEMASYARAKATAN - Subroto, Mitro; Hasman, Tsaqif Addafa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This study examines the impact of limited access on the rehabilitation of disabled inmates in correctional facilities. The urgency of this research stems from the increasing number of disabled individuals within the prison system, highlighting a gap in rehabilitation services tailored to their needs. A qualitative approach was employed, utilizing interviews with inmates and staff, as well as document analysis to gather data. The findings reveal significant barriers, including inadequate facilities and lack of specialized programs, which hinder effective rehabilitation. The study concludes that improving accessibility and implementing targeted rehabilitation programs are essential for enhancing the reintegration of disabled inmates into society.Keywords: disabled inmates; rehabilitation; access barriers; correctional facilities; social reintegration